KelasMimpi: Early Marriage Prevention Program through Self-Realization Awareness at Wongsorejo Village, Banyuwangi - Hemalia Kusumadewi; Wishnu Mahendra Wiswayana (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2025)
This community service project centered on the urgent need to reduce and prevent early marriage cases in Wongsorejo Village, Banyuwangi Regency. This is due to the high number of early marriage cases and its devastating effects on Wongsorejo citizens, especially children and teenagers, such as school dropouts, higher divorce rates, higher youth pregnancy complication rates, and even stunting. Since girls are highly likely to be victims of early marriage, gender inequality is a concern that needs to be addressed immediately. This community service aims to eliminate the potential factor of extra-marital pregnancy, which is one of the early marriage main causes in Wongsorejo. This is due to the root causes of low awareness about early marriage and young pregnancy among children and teenagers. Thus, KelasMimpi provides a solution by enhancing teenagers’ awareness of early marriage, emphasizing the importance of self-realization, and demonstrating how to apply it in their daily lives. This program is aligned with Sustainable Development Goal 5, ‘Equality,’ Target 5.3, ‘Eliminate all harmful practices, such as child, early and forced marriage and female genital mutilation.’ This program employs a service learning approach with three implementation methods: informative education sessions, focus group discussions, and interactive discussions. Questionnaires were used as the main impact evaluation method. KelasMimpi yields significant results in changing teenagers’ perceptions of early marriage and their self-realization ability.